Perspektif Ulama Terhadap Akad Murabahah untuk Modal Usaha Mikro - M. Yusuf Azwar Anas (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2016)
Muamalah fiqh studies on murabaha contracts apply the principle of buying and selling, mudharabah and musyarakah contracts are contracts that apply a profit-sharing system and are usually used to finance venture capital. However, along with the development of Islamic banks, the murabaha contract in its application has changed. As at present murabahah contracts are used to finance business capital. The purpose of this research is to find out the shari'ah provisions on the implementation of murabahah contracts on business capital financing products with a case study at PT.BPRS Bumi Rinjani. This type of qualitative research uses the hermeneutic method, namely interpreting, giving understanding or translating a problem. This study also uses a triangulation analysis tool, namely the technique of checking the validity of the data. The results of this study note that the use of a murabaha contract for business capital has two opinions, one allows and the other does not allow, the opinion that allows the reason that is financed using a sale and purchase with a murabahah contract is the need for business working capital such as trading. While the opinion that does not allow reasons and pillars of murabaha is not appropriate if it is used for business capital because profits cannot be shared in two as in musyarakah or mudharabah. So to maintain the sharia of a contract it is better to use a mudharabah or musyarakah contract for providing capital. In this study also found new findings, the use of wakalah contracts in murabaha, with two opinions as well, one allows and the other does not allow. However, to maintain the sharia of a contract, it is better that murabahah is carried out after the wakalah contract and after the bank already has the object, then the murabaha contract is carried out, so that it does not go out of sharia provisions.